Ruptures of the pectoralis major and minor muscles - Sanchez Carbonel, José Fernando (2023)
The pectoralis major (PMa) and pectoralis minor (PMi) muscles differ from each other in almost every aspect, despite the fact that they are localized very close to each other. While indirect traumatic injury is more common in PMa rupture, PMi avulsion via direct trauma injury is more frequently documented. Despite the low activity of the PMa during everyday movements, the patient’s cosmetic satisfaction and functional results are significantly better with surgical treatment compared to conservative treatment. On the other hand, conservatively treated patients after a PMi rupture have no functional restrictions and are therefore satisfied with the nonsurgical treatment. The surgical options for PMa ruptures are often explained in three main forms of treatment, the transosseous suture, the suture anchor and the unicortical or bicortical button. Due to the insufficient number of studies, a standard procedure has not yet been identified at the current time.